Interdependencia estratégica y escenarios en la implementación tecnológica ganadera - Perez, Santiago Agustín (Pontificia Universidad Católica del Perú, 2025)
This paper analyses the implementation of electronic caravans in the Argentine cattle sector using game and scenario theory. It explores Senasa’s decisions on the mandatory or voluntary nature of the regulations and the responses of producers: forced, autonomous adoption or rejection. The model is developed in six stages, from the definition of the problem to the evaluation of results, considering economic, social and territorial implications of each strategy. The results indicate that electronic caravans improve traceability, facilitate access to international markets, reduce health costs and increase competitiveness. However, the impacts vary depending on the implementation; mandatory standardization standardizes the system but imposes initial costs, while autonomous adoption encourages innovation but could generate inequities. The paper highlights the need for policies that encourage cooperation, incentives for technological adoption and clear regulations that align individual and collective interests.

Este trabajo analiza la implementación de caravanas electrónicas en el sector ganadero bovino argentino utilizando teoría de juegos y escenarios. Se exploran las decisiones del Senasa sobre la obligatoriedad o voluntariedad de la normativa y las respuestas de los productores: adopción forzada, autónoma o rechazo. El modelo se desarrolla en seis etapas, desde la definición del problema hasta la evaluación de resultados, considerando las implicancias económicas, sociales y territoriales de cada estrategia. Los resultados indican que las caravanas electrónicas mejoran la trazabilidad, facilitan el acceso a mercados internacionales, reducen costos sanitarios y aumentan la competitividad. Sin embargo, los impactos varían según la implementación; la obligatoriedad estandariza el sistema, aunque impone costos iniciales; mientras que la adopción autónoma fomenta la innovación, pero podría generar inequidades. El trabajo subraya la necesidad de políticas que fomenten la cooperación, incentivos para la adopción tecnológica y regulaciones claras que alineen intereses individuales y colectivos.
Strategic interdependence and scenarios in livestock technology implementation
Keywords: Game theory; Foresight; Innovation; Competitiveness; Livestock network; Teoría de juegos; Prospectiva; Innovación; Competitividad; Entramado ganadero; https://purl.org/pe-repo/ocde/ford#5.02.04